Guide RNA Repertoires in the Main Lineages of Trypanosoma cruzi: High Diversity and Variable Redundancy Among Strains - Rusman, Fanny; Floridia-Yapur, Noelia; Tomasini, Nicolás; Diosque, Patricio (Frontiers in Cellular and Infection Microbiology, 2021)
Trypanosoma cruzi, as other kinetoplastids, have a complex mechanism of edition of mitochondrial mRNAs that requires guide RNAs (gRNAs) coded in DNA minicircles in the kinetoplast. There are many variations on this mechanism among species. mRNA edition and gRNA repertoires are almost unknown in T. cruzi. Here, we have inferred gRNAs based on deep-sequenced minicircle hypervariable regions (mHVRs) and rebuilt edition cascades in strains belonging to the six main T. cruzi lineages. Inferred gRNAs were clustered according to their sequence similarity to constitute gRNA classes. We detected extreme diversity of gRNA classes and highly divergent gRNA repertoires among different lineages, even within some lineages. In addition, we observed variable gRNA class redundancy (i.e., different gRNA classes editing the same mRNA region) among strains. Some strains had upon four times more gRNA classes than others. Such variations in redundancy affected gRNA classes of all mRNAs in a concerted way, i.e., there are correlated variations in the number of gRNAs classes editing each mRNA. Interestingly, we failed to rebuild complete cascades for components of the respiratory complex I in several strains. Finally, we observed that gRNA classes of different strains may potentially edit mitochondrial mRNAs from other lineages in the same way as they edit their own mitochondrial mRNAs, which is a prerequisite for biparental inheritance of minicircle in hybrids. We propose that genetic exchange and biparental inheritance of minicircles combined with minicircle drift due to (partial) random segregation of minicircles during kDNA replication is the more suitable hypothesis to explain the divergences among strains and the high levels of gRNA redundancy in some strains. Such redundancy may act as a buffer to reduce the lethality caused by essential gRNA class lost. In addition, our results support that the complex I may not be required in some stages in the life cycle as previously shown and that linkage (in the same minicircle) of gRNAs that edit different mRNAs may prevent gRNA class lost in such stage.